Effects of Blended Learning on the Self-Directed Learning and Academic Achievement of First-Year Nursing Students Studying Metabolic Biochemistry - Chaopipat, Yuree; Tokun, Pimrat; Srithahai, Jerapa (Journal of Education Studies, Chulalongkorn University, 2025)
This study examined the impact of blended learning on the self-directed learning and academic achievement of the first-year nursing students studying metabolic biochemistry. This quasi-experiment research recruited 150 first-year nursing students at one of the nursing college. A blended learning intervention, combining face-to-face instruction and various online activities, was implemented. Data were collected using a self-directed learning scale, pretest and posttest, and a final exam. Results indicated that blended learning significantly enhanced students’ self-directed learning (t = -2.847, p = 0.005) and academic performance. Post-test scores across all chapters significantly improved after the intervention (t = -10.63, p = 0.000). Additionally, weak positive correlations were found between self-directed learning scores and final exam scores (r = 0.25, p = 0.003), as well as between posttest scores and final exam scores (r = 0.29, p = 0.000). These findings suggest that blended learning is a promising approach to foster self-directed learning and improve student outcomes in metabolic biochemistry. Educators at both the secondary and tertiary levels can adapt and apply the blended learning activities employed in this study to suit their specific subject matter and student characteristics, thereby enhancing students’ ability in self-directed learning.